2017
DOI: 10.20885/jkki.vol8.iss2.art4
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of dermatological infection in outpatient dermatology clinic of RSUD Wonosari in January-September 2016

Abstract: Original ArticleNoegroho, et al. amounted to 303 cases. The cases consisted of 127 cases of fungal infection (42%) with a variety of cases of dermatophytosis, PVC, and candidiasis; 55 cases of bacterial infections (18%) with a variety of cases of impetigo, folliculitis, leprosy, ektima, erysipelas, furuncles, and abscesses; 40 cases of viral infections (13%) with variaty of cases of HFMD cases, Moluscum contagiosum, zooster, warts, varicella; and 81 cases of parasitic infections (27%) with a variety of cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Another study carried out by Noegroho et al (2017) in Gunung Kidul, Indonesia, yielded varied results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study carried out by Noegroho et al (2017) in Gunung Kidul, Indonesia, yielded varied results.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent presentation of the infection was tinea corporis, which was mostly observed in patients aged 1-10 years. In a separate study carried out by Noegroho et al (2017) at Wonosari Regional General Hospital, Gunung Kidul, Indonesia, 303 cases of skin infections were documented. Out of the 303 cases, fungal infections were reported in 127 (42%) individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A study in a secondary hospital in Yogyakarta, Indonesia reported that fungal infection was the most common skin infection (42%), consisting of dermatophytosis, pityriasis versicolor and candidiasis. 9 As the prevalence of a disease and its related factors are important data needed to develop strategies for disease management and prevention, this multicentre retrospective study aimed to obtain the prevalence and factors associated with mucocutaneous mycoses among PLHIV in Indonesia.…”
Section: Introductionmentioning
confidence: 99%